Modified stabilization method for the tibial tuberosity advancement technique: a biomechanical study - Bruno Testoni Lins (Ciência Rural, 2009)
The present study aimed to determine biomechanical alterations resultant from a modification in the fixation method of the tibial tuberosity advancement technique (TTA), originally described for stabilization of the cranial cruciate-deficient stifle. Ten adult mongrel dogs weighing 25-30kg were used. After euthanasia, performed for reasons unrelated to this study, the hind limbs were distributed into two groups: G1 operated (n=10) and G2 control (n=10), represented by the contralateral limb. The operated hind limbs were orthopedically, goniometrically and radiographically evaluated, sequentially at four moments: moment 1, in intact joints; moment 2, after cranial cruciate desmotomy; moment 3, after surgical stabilization of the stifle joint using modified TTA; and moment 4, after caudal cruciate ligament desmotomy. The tibial tuberosity was stabilized by one shaft screw craniocaudally and a titanium cage inserted at the osteotomy site. The position of the patellar tendon at 90° in relation to the tibial plateau allowed cranial tibial thrust force neutralization, despite cranial drawer motion maintenance in all dogs. The biomechanical tests confirm the viability of the tibial tuberosity fixation method and support future clinical trials to validate the technique.